MiR‐483‐5p and miR‐139‐5p promote aggressiveness by targeting N‐myc downstream‐regulated gene family members in adrenocortical cancer. Issue 4 (30th March 2018) - Agosta, Claire; Laugier, Jonathan; Guyon, Laurent; Denis, Josiane; Bertherat, Jérôme; Libé, Rossella; Boisson, Bruno; Sturm, Nathalie; Feige, Jean‐Jacques; Chabre, Olivier; Cherradi, Nadia
Abstract : Adrenocortical carcinoma (ACC) is a tumor with poor prognosis in which overexpression of a panel of microRNAs has been associated with malignancy but a very limited number of investigations on their role in ACC pathogenesis have been conducted. We examined the involvement of miR‐483‐5p and miR‐139‐5p in adrenocortical cancer aggressiveness. Using bioinformatics predictions and mRNA/miRNA expression profiles, we performed an integrated analysis to identify inversely correlated miRNA–mRNA pairs in ACC. We identified N‐myc downstream‐regulated gene family members 2 and 4 (NDRG2 and NDRG4) as targets of miR‐483‐5p and miR‐139‐5p, respectively. NDRG2 and NDRG4 expressions were inversely correlated respectively with miR‐483‐5p and miR‐139‐5p levels in aggressive ACC samples from two independent cohorts of 20 and 44 ACC. Moreover, upregulation of miR‐139‐5p and downregulation of NDRG4 demonstrated a striking prognostic value. A direct interaction between miR‐483‐5p or miR‐139‐5p and their targets was demonstrated in reporter assays. Downregulation of miR‐483‐5p or miR‐139‐5p in the ACC cell lines NCI‐H295R and SW13 increased NDRG2 or NDRG4 mRNA and protein expression, compromised adrenocortical cancer cell invasiveness and anchorage‐independent growth. MiR‐483‐5p or miR‐139‐5p overexpression and NDRG2 or NDRG4 inhibition produce similar changes, which are rescued by NDRG2 or NDRG4 ectopic expression. We established that key factors mediating epithelial‐to‐mesenchymal transition are downstream effectors of miR‐483‐5p/NDRG2 and miR‐139‐5p/NDRG4 pathways. Collectively, our data show for the first time that miR‐483‐5p/NDRG2 and miR‐139‐5p/NDRG4 axes promote ACC aggressiveness, with potential implications for prognosis and therapeutic interventions in adrenocortical malignancies. Abstract : What's new? Little is known about the contribution of microRNA dysregulation to the pathogenesis of adrenocortical carcinoma (ACC), a highly aggressive malignancy. This work provides first evidence that two overexpressed microRNAs, miR‐483‐5p and miR‐139‐5p, respectively target two members of the N‐myc downstream‐regulated gene family, NDRG2 and NDRG4. Key factors mediating epithelial‐to‐mesenchymal transition are downstream effectors of miR‐483‐5p/NDRG2 and miR‐139‐5p/NDRG4 pathways. miR‐483‐5p and miR‐139‐5p promote ACC migration and invasion by suppressing NDRG2 and NDRG4 expression. Both target genes are strikingly under‐expressed in patients with aggressive tumors. Thus, miR‐483‐5p/NDRG2 and miR‐139‐5p/NDRG4 axes may represent novel targets for therapeutic intervention in ACC with poor outcome.